1974
DOI: 10.1007/bf00203996
|View full text |Cite
|
Sign up to set email alerts
|

Supergene alteration of the Mt Windarra nickel sulphide ore deposit, Western Australia

Abstract: Three main zones of progressive oxidation, termed the transition, violaritepyrite and oxide zones, can be delineated in the supergene profile o£ the Mt Windarra massive/matrix ore deposit. In the broad transition zone from pure primary ore, pentlandite is progressively oxidised to an iron rich violarite of composition Co0.0eFel.asNil.60 $4, releasing Fe 2+ and Ni 2+ ions into solution. Up to 43 % of this Ni 2+ moves to nearby pyrrhotite margins which are replaced firstly by nickeliferous smythite and then by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…Eh measurements have shown that the oxidation potential in a nickel sulphide deposit undergoing weathering increases upward (Thornber, 1975), and mineralogical observations have confirmed that the original sulphide assemblage changes to a more highly oxidized one toward the water table (Nickel et al, , 1977aWatmuff, 1974;Thornber, 1975).…”
Section: Below the Water Tablementioning
confidence: 96%
See 2 more Smart Citations
“…Eh measurements have shown that the oxidation potential in a nickel sulphide deposit undergoing weathering increases upward (Thornber, 1975), and mineralogical observations have confirmed that the original sulphide assemblage changes to a more highly oxidized one toward the water table (Nickel et al, , 1977aWatmuff, 1974;Thornber, 1975).…”
Section: Below the Water Tablementioning
confidence: 96%
“…Changes in the sulphide mineralogy (below the water table) have been well documented (Nickel et al, , 1977aWatmuff, 1974;Thornber, 1975).…”
Section: Mineralogical and Chemical Variations In The Weathered Profilementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, chalcopyrite is often retained when pentlandite is altered to violarite (Table 4). This may be related to weathering-related aerated oxidizing conditions, in which violarite is typically formed (Watmuff, 1974).…”
Section: Effect Of Low-temperature Alterationmentioning
confidence: 99%
“…Thornber, 1972;Nickel et al, 1974;Watmuff, 1974;Thornber, 1975a). Such sulphide deposits exhibit the following features that promote deep oxidation: (a) at least one of the primary sulphides is characterized by a high metal: sulphur ratio, which enables oxidation reactions to take place at oxidation potentials below that at which sulphur oxidizes; (b) the massive sulphide assemblage provides a continuous conductor for the electrons generated by the anodic reactions; and (c) the top end of the orebody intersects the water table where there is abundant oxygen for the cathodic reactions to take place.…”
Section: Sulphide Oxidation the Electrochemical Mechanismmentioning
confidence: 99%